Genetical stability and osteogenic ability of mesenchimal stem cells on demineralized bone matrices - A. Pozzuoli; C. Gardin; R. Aldegheri; E. Bressan; M. Isola; J. L. Calvo-Guirado; C. Biz; P. Arrigoni; L. Feroni; B. Zavan (Journal of Osseointegration, 2015)
Aim Tissue engineering is a rapidly expanding field with regard to the use of biomaterials and stem cells in the orthopedic surgery. Many experimental studies have been done to understand the best characteristics of cells, materials and laboratory methods for safe clinical applications. The aim of this study was to compare the ability of 2 different human demineralized bone matrices (DBMs), the one enriched and the other not enriched with hyaluronic acid, to stimulate in vitro the proliferation and the osteogenic differentiation of human adipose-derived stem cells (ADSCs) seeded onto an osteoconductive scaffold. Materials and Methods ADSCs were isolated, by enzymatic digestion, from abdominal adipose tissue of 5 patients undergoing cosmetic lipoaspiration surgery. ADSCs were then seeded onto a 3D scaffold in the presence of the two different osteoinductive matrices of human demineralized bone and evaluated for proliferation and osteogenic differentiation. The safety of the methods was verified using array-Comparative Genomic Hybridization (array-CGH). Results ADSCs were able to differentiate in osteogenic sense. Both DBMs showed the ability to induce osteogenic differentiation of the cells. Conclusion array-CGH showed no changes at genome level, thus confirming the safety of materials and methods.